PENINGKATAN KELARUTAN KALSIUM MELALUI PENAMBAHAN DAUN KETAPANG Terminalia catappa PADA MEDIA AIR TAWAR BUDIDAYA UDANG VANNAMEI Litopennaeus vannamei - Andre Rachmat Scabra; Muhammad Marzuki; Nunik Cokrowati; Bagus Dwi Hari Setyono; Laily Fitriani Mulyani (Universitas Mataram, 2021)
Litopenaeus vannamei is a high-economic fishery commodity that has euryhaline properties, which is tolerant of a wide range of salinity values ??(2 – 40 ppt). The euryhaline of vannamei shrimp are still not well optimized. The purpose of this study was to determine the appropriate dose of ketapang leaf addition to increase mineral solubility in freshwater vannamei shrimp culture medium. The results of this study are expected to be useful as information for vannamei shrimp cultivators in freshwater media about technology for meeting mineral levels in the media so as to maximize production value. This study used a completely randomized design (CRD) method which consisted of 4 treatments and 3 replications. The treatment applied was the addition of ketapang leaves with different doses to increase the solubility of calcium carbonate (CaCO3) in cultivation media, namely A. Ketapang leaves (DK) 0 ppt + CaCO3 50 ppm; B. DK 120 ppm + CaCO3 50 ppm; C. DK 240 ppm + CaCO3 50 ppm; D. DK 360 ppm + CaCO3 50 ppm. The results showed that the appropriate dose of ketapang leaves that could increase mineral solubility in freshwater vannamei shrimp culture media was 360 ppm (treatment D). At this dose, the value of the specific weight growth rate of vannamei shrimp can increase, which is 0.76%/day. Treatment A is a control treatment that gives the lowest value for the specific weight growth value, which is 0.40 %/day.